Why OECD GLP and not ISO / IEC 17025? - Liddy, Helen (Henry Stewart Talks, 2012)
Principles of GLP v ISO/IEC 17025, Similarities and differences, OECD discussion paper, Implementing a combined GLP/ISO 17025 quality system